Honorification in Nepali: a psycholinguistic perspective - Pathak, Lekhnath Sharma (Gipan, 2019)
This research article explores the psycholinguistic processes of honorification manipulation in Nepali language. Honorification is not static but dynamic process and is affected by many factors including psychological. Data is drawn from published narratives, mostly in the Nepali media, and analyzed from psycholinguistic perspective. The range of data include politics, royalese, language of marital discord and media. Significant influencers in choice of honorifics are fluctuation in state of mind and proximality. The canonical three-level honorific system is discussed as a reference point for psychologically motivated honorification fluctuation. Three types of honorific operators are identified and discussed: psychological, royalese and neutralization. The article attempts to bring forth the complex mechanisms that work on the honorification system in Nepali language.